The influence of the Peroneus Longus muscle on the foot under axial loading: A CT evaluated dynamic cadaveric model study. (May 2016) - Dullaert, K.; Hagen, J.; Klos, K.; Gueorguiev, B.; Lenz, M.; Richards, R.G.; Simons, P.
Abstract: Background : Subtle hypermobility of the first tarsometatarsal joint can occur concomitantly with other pathologies and may be difficult to diagnose. Peroneus Longus muscle might influence stability of this joint. Collapse of the medial longitudinal arch is common in flatfoot deformity and the muscle might also play a role in correcting Meary's angle. Methods : A radiolucent frame was used to simulate weightbearing during CT examination. Eight pairs fresh-frozen lower legs were imaged in neutral position under non-weightbearing (75 N), weightbearing (700 N) and with 15 kg weights hung from Peroneus Longus tendon. Measurements included first metatarsal rotation, intermetatarsal angle, first tarsometatarsal joint subluxation and Meary's angle. Findings : Weightbearing significantly increased Meary's angle and significantly decreased first tarsometatarsal joint subluxation (both P < 0.01). Pulling Peroneus Longus tendon significantly increased first metatarsal rotation ( P < 0.01), significantly decreased the intermetatarsal angle ( P < 0.01) and increased non-significantly Meary's angle ( P = 0.52). Interpretation : A considerable effect weightbearing has on the medial longitudinal arch and first tarsometatarsal joint was observed. Pulling Peroneus Longus tendon improved first metatarsal subluxation but increased its rotation. The study calls into question the importance of this tendon in maintaining the medial longitudinal arch and raises concerns about rotational deformity of the first metatarsal following hallux valgus correction without first tarsometatarsal arthrodesis. Clinical relevance : Study outcomes will provide more insight in foot pathology. What is known about the subject : Weightbearing affects anatomy of the foot. No reliable information is available concerning the influence of the Peroneus muscle. What this study adds to existing knowledge : This study investigates the influence of weightbearing and the impact the Peroneus muscle on the anatomy of the foot. Highlights: Significant effect of weightbearing is simulated. Weightbearing alters medial longitudinal arch and first TMT joint positions. Peroneus Longus tendon actuation improves the first TMT joint sagittal plane subluxation and the intermetatarsal angle. Peroneus Longus tendon actuation increases first metatarsal rotation. Peroneus Longus tendon actuation does not reconstitute the medial arch.